Giovanni Barbieri (2021), The Fifth Cleavage. Genealogy of the Populist Ideology and Parties, London: Lexington Books. - Millefiorini, Andrea (PARTECIPAZIONE E CONFLITTO, 2022)
For Book Reviews Abstract is not required